Effectiveness of Essential Oil Aromatherapy in Reducing Labor Pain Among Women Giving Birth at Zhafira Zharifa Clinic - Rina Dwi Anggraeni; Dewi Rubi Fitriani; Marliana Rahma; Mutiara Balqis H Ronika; Indah Istari (Jurnal Kesehatan dan Kedokteran, 2025)
Labor pain is a natural component of childbirth; however, excessive pain may negatively affect maternal physical and psychological well-being. Effective pain management is therefore essential to improve maternal comfort and promote a positive childbirth experience. Essential oil aromatherapy has emerged as a complementary therapy that may reduce pain perception through physiological and psychological relaxation mechanisms. This study aimed to analyze the effectiveness of essential oil aromatherapy in reducing labor pain among women giving birth at Zhafira Zharifa Clinic. This study employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. A total of 30 women undergoing normal labor participated in the study. Labor pain intensity was assessed before and after the administration of essential oil aromatherapy through inhalation. Data were analyzed using descriptive statistics and a Paired Sample t-Test with a significance level of 0.05. The results revealed that the mean labor pain score decreased from 67.8 before the intervention to 48.6 after the administration of aromatherapy. Statistical analysis demonstrated a significant difference between pretest and posttest pain scores (p = 0.000). These findings indicate that essential oil aromatherapy effectively reduces labor pain among women during childbirth. The reduction in pain intensity may be associated with the stimulation of the limbic system, which promotes relaxation and enhances the release of endorphins and serotonin, thereby decreasing pain perception. The findings suggest that essential oil aromatherapy can be integrated into maternity care as a safe, simple, non-invasive, and cost-effective complementary intervention for labor pain management. The originality of this study lies in its evaluation of aromatherapy effectiveness within a primary healthcare maternity setting using a pretest–posttest approach and direct measurement of labor pain intensity. The study contributes additional empirical evidence supporting the use of complementary therapies in improving maternal comfort during childbirth.